Health-Related Fitness in Adults From Eight European Countries—An Analysis Based on Data From the European Fitness Badge - Klemm, Katja; Krell-Roesch, Janina; De Clerck, Ine Lucia; Brehm, Walter; Boes, Klaus (Frontiers in Physiology, 2021)
Background: There are conflicting reports about the fitness status of European adults, partly due to the lack of a standardized fitness test battery used across Europe. The European Fitness Badge (EFB) was developed in 2017 as an online-based tool to assess the health-related fitness of persons aged ≥ 18 years residing in European countries. We examined the demographic characteristics and fitness status of persons who completed the EFB between June 2017 and May 2019. Methods: We conducted a multinational study in eight European countries. Participants completed the EFB which includes eleven validated motor tests to measure endurance, strength, coordination and flexibility performance, under the supervision of an EFB instructor in different settings (e.g. sports club sessions, public events). Two different test batteries (test profiles, TP) are available to distinguish between less active (TP1) and active individuals (TP2). We calculated descriptive statistics and conducted analyses of variance to examine sample characteristics and a potential impact of sex, age, body mass index (BMI), physical activity and posture on fitness as assessed by the EFB. Results: The sample included 6,019 adults (68.7% females; mean age 52.7 years; age range 18-89 years). Participants who completed TP1 were older (TP1: 61.4 years; TP2: 44.2 years; p = 0.00), reported a lower level of physical activity (TP1: 3.8; TP2: 4.0; p = 0.00), had a higher BMI (TP1: 25.7; TP2: 24.3; p = 0.00) and a higher frequency of postural abnormalities (TP1: 43%; TP2: 33%; p = 0.00) than TP2 participants. Among 3,034 participants who completed TP2, males had higher performance in endurance, strength and overall fitness, whereas females performed better in coordination and flexibility tests. In addition, younger age, lower BMI and higher level of physical activity engagement was associated with better EFB test performance. Conclusions: The EFB can be used to assess the health-related fitness status of individuals aged ≥ 18 years. Our results show that TP1 and TP2 were completed by persons from the respective target groups (i.e. less active vs. active), and also confirm findings from previous studies on potential determinants of fitness such as sex or age.